The Influence of Marketing Strategies (Promotion, Product Quality, Price) and Product Diversity on Consumer Purchase Decisions at PT. Vincy Glow Lamongan - Aan Andri Ardiyansah; Abid Muhtarom; Mohammad Yaskun (Sean Institute, 2025)
A purchase decision is a decision-making process where the buyer will actually buy. Many factors influence the purchase decision of a product such as: promotion, product quality, price and product diversity. The type of research used in this study is quantitative. The population in this study is Vincy Glow consumers. and the sample used in this study was 100 consumers. From the results of the t-test, it was obtained that there was a partially significant influence between the variables of Promotion (X1), Product Quality (X2), Price (X3) and Product Diversity (X4) on Purchase Decision (Y) on Vincy Glow. The variables of free promotion, product quality, price and product diversity have a simultaneous influence on the Purchase Decision. This can be proven by the value of Fcal ˃ Ftable with a significant level of less than 0.05, which is 0.000. From the multiple linear regression equation, the result of the product quality variable (X2) = 0.446 is greater than the other variables. So it can be concluded that product quality (X2) is the most dominant variable affecting the Purchase Decision (Y) in Vincy Glow Lamongan.